2021
DOI: 10.1007/s12262-021-03047-y
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Surgical Trainees: a Narrative Review of Trends, Contributors, Consequences and Possible Interventions

Abstract: Surgical disciplines are popular and training places are competitive to obtain, but trainees report higher levels of burnout than either their non-surgical peers or attending or consultant surgeons. In this review, we critically summarise evidence on trends and changes in burnout over the past decade, contributors to surgical trainee burnout, the personal and professional consequences of burnout and consider the evidence for interventions. There is no evidence for a linear increase in burnout levels in surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…The present review extends these findings by reporting on these associations in surgeons specifically, which are a group known to report higher levels of burnout than other medical specialties 48 .…”
Section: Comparisons With Previous Reviewssupporting
confidence: 57%
See 1 more Smart Citation
“…The present review extends these findings by reporting on these associations in surgeons specifically, which are a group known to report higher levels of burnout than other medical specialties 48 .…”
Section: Comparisons With Previous Reviewssupporting
confidence: 57%
“…To date, the great majority of studies have been in high-income countries [54][55][56] , but these may not translate to other nations. Finally, a recent review has shown that surgical trainees are more burned out than their non-surgical counterparts 48 , therefore, healthcare providers ought to also explore how training programmes can be modified to help support trainees earlier in their careers.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…The mentality and mindset of pragmatic surgery professionals may be more compatible with an intervention approach that focuses on “what can be done” to deal with stress and burnout at work. 24 The findings from our study suggest interventions should be designed to be low-stigma as we found that surgeons were reluctant to talk about current burnout. Resilience-building training may therefore be less stigmatising than interventions promoted as “burnout support” interventions and more acceptable to surgeons.…”
Section: Discussionmentioning
confidence: 70%
“…23 Therefore, there is clearly a need for more and higherquality studies investigating burnout treatments in surgeons and surgical trainees. 24 The second question this study attempted to answer was: how does burnout affect the care that surgeons provide? These findings support studies that have found that burnout has a negative impact on patient satisfaction and surgical professionalism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation